Development of NMDA receptors contributes to the enhancement of electroencephalogram oscillations under volatile anesthetics in rats - Zhang, Mingyue; Chen, Yali; Liu, Jin; Yang, Yaoxin; Wang, Rurong; Zhang, Donghang; Zhu, Tao (Frontiers in Neural Circuits, 2022)
Background: Volatile anesthetics including sevoflurane and isoflurane enhance oscillations of cortical electroencephalogram (EEG), partly by their modulations on glutamate-mediated excitatory synaptic transmission. Expression of NMDA receptors is increased during neonatal development. However, how the development of NMDA receptors influences EEG under volatile anesthesia remains unclear. Methods: Expressions of NMDA receptor subtypes (NR1, NR2A and NR2B) during neonatal development were measured by Western blotting. MAC (minimal alveolar concentration) of isoflurane and sevoflurane that inducing loss of righting reflex (LORR) and no response to tail-clamp (immobility) were measured to verify the effect of NR1 expression on anesthetic potency during neonatal development. Cortical electroencephalogram recording was used to examine the influence of NR1 expression on the power density of EEG. Results: The expressions of GluNR1, GluNR2A and GluNR2B receptors were gradually increased during neonatal development in cortex, hippocampus and thalamus of rats. Knockdown of NR1 enhanced the sedative potency of volatile anesthetics but not on immobility potency in postnatal day 14 (P14)-P17 rats. For cortical EEG, along with the increased concentration of volatile anesthetics, cortical slow-delta oscillations of P5 rats were inhibited, theta and alpha oscillations were not changed significantly; while these oscillations were enhanced until high anesthetic concentrations in P21 rats. Knockdown of NR1 in forebrain suppressed the enhancement of cortical EEG oscillations in P21 rats. Conclusions: The development of NMDA receptors may contribute to the enhancement of cortical EEG oscillations under volatile anesthetics.